2006
DOI: 10.1177/095207670602100103
|View full text |Cite
|
Sign up to set email alerts
|

The Public Service Ethos in the British Civil Service: An Historical Institutional Analysis

Abstract: This articler traces the origins, development and decline of the public service ethos in the British civil service and the extent to which it has been supplanted by a new set of values, beliefs and institutional relationships since the 1980s. The modem civil service dates from the mid-nineteenth century and has evolved to meet the changing needs ofthe state as it has movedfrom a regulatory to a social service to a welfare state and now to an enabling state over the last 150 years. Some periods were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…There is a tendency that the professionals hybridize and incorporate governing principles linked to these values (Kurunmäki, 2004). This is a consequence of a development where civil servants are exposed to more diverse accountabilities than before for their managerial and administrative actions (Horton, 2006).…”
Section: Institutional Logicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a tendency that the professionals hybridize and incorporate governing principles linked to these values (Kurunmäki, 2004). This is a consequence of a development where civil servants are exposed to more diverse accountabilities than before for their managerial and administrative actions (Horton, 2006).…”
Section: Institutional Logicsmentioning
confidence: 99%
“…Public service reforms in a number of countries have sought to dilute the traditional power of professionals and increase managerial power (Horton, 2006). This has allegedly led to traditional high levels of trust being replaced by mistrust, rigorous control and audit devices, a practice now being questioned by leading political scientists (Fukuyama, 2013).…”
Section: Institutional Logicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion has long historical roots that extend back to the formation of the civil service in the mid-nineteenth century which has evolved and been institutionalised in a number of ways (Morgan and Allington 2002;Horton 2006;Davies 2012). The Royal Commission on the Civil Service, for example, stated that while a 'good employer' need not necessarily offer its employees high rates of pay, it did have to provide job security, joint consultation in the form of collective bargaining and 'facilities and opportunities for training' (Priestley 1955, 172).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Carr (1999) and Horton (2006a) studied the development of the public service ethos in Britain. Both concluded that market orientation has affected the traditional public service ethos, but has prevailed because its importance is acknowledged both by civil servants and by public opinion.…”
Section: Ethos In the Finnish Public Administrationmentioning
confidence: 99%